Análisis del manejo de prácticas agrícolas para mejorar el rendimiento de la palma aceitera en la zona de Los Ríos - Carbo Burgos, Norma Elizabeth (2020)
This study had the purpose of being able to cooperate from the technical-agricultural point of view with the producers of oil palm cultivation of the Province of Los Ríos, in order to provide possible solutions regarding the management of cultural tasks applied in cultivation, During the study, it was observed that the production factors were not carried out in a technical way, which led to a decrease at harvest time, which ends up being reflected in economic losses, which are reflected in costs. production of the producer, and even many times due to the execution of poor agricultural tasks, not only money but also time is lost, for that reason this work tries to provide an organized approach from sowing to postharvest, involving all those cultural tasks that involve good crop management in order to cope with the demands received from the oil palm industries. Observing the importance of this crop, at the end of this bibliographic work it was recommended to carry out field days, socialization of flyers on good agricultural practices, links with the community and undergraduate thesis to improve as much as possible the problem raised.